Peran Komunikasi dalam Kelembagaan Petani pada Pengembangan Kakao di Kabupaten Kolaka Timur - Arimbawa, Putu; Hidayat, Kliwon; Cahyono, Edi Dwi; Yuliati, Yayuk; Daud, L (Jurnal Ilmiah Membangun Desa dan Pertanian, 2020)
The purpose of this study is to analyze the role of communication in the information management process that occurs in farmer institutions to support cocoa development. This research is a survey research with a questionnaire as a data collection tool. The research location is in East Kolaka Regency with the target of LEMS cocoa farmers. The research location is in East Kolaka Regency with the target of LEMS cocoa farmers. Sampling as many as 267 farmers spread over 18 LEMS by proportional random sampling. Descriptive research data analysis. The results showed that the role of communication in LEMS institutions was in the medium category cocoa development. The role of communication that needs to be improved is the role in accessing information and mediating information. Information management is still dominantly sourced from explicit knowledge and does not accommodate knowledge from farmers' experience (tacit knowledge).